Poverty Trends and Disparities in Southeast Sulawesi Province - Muljibir Rahman; Al Quadhri; Mahfudz (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Poverty remains a persistent structural issue and represents a significant challenge for regional development, including in Southeast Sulawesi Province. Although the national poverty rate has shown a declining trend, disparities and fluctuations continue to occur at the district/city level. Objectives: This study aims to examine the development of poverty levels across 17 districts and cities in Southeast Sulawesi Province during the period 2019–2023 and to identify regions with the highest and lowest incidence of poverty. Methods: The study employs a descriptive quantitative approach using secondary data obtained from the Central Statistics Agency (BPS). Analytical methods include trend analysis and spatial comparison across districts and cities. Results: The number of individuals living in poverty in Southeast Sulawesi exhibited fluctuations over the five-year period. The most significant increase occurred in 2021, attributed to the socio-economic impact of the COVID-19 pandemic. Muna and South Konawe Regencies recorded the highest poverty figures, while the Konawe Islands Regency consistently had the lowest. Spatial disparities and the varying effectiveness of social assistance programs contributed to these differences. Conclusion: The findings highlight the need for region-specific strategies and the optimization of inclusive socio-economic development programs to sustainably reduce poverty in Southeast Sulawesi.